Human Security Identification in Maqoshid Sharia Concept as Implementation in Debt Trap of Digital Finance - Dwi Ardiyanti; Surwandono Surwandono; Puspa Devi Maharani; Novi Rizka Amalia (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
The research aims to identify the relationship between the phenomenon of digital finance on the debt trap with the study of human security in the Islamic concept. Cybercrime harms many people by misusing personal data that can be accessed online illegally, such as loan applications, digital shopping, or digital wallet. The debt trap resulted in the application then best analyzed through human security of international relations. The study focused on human security, such as personal and economic security. The study concluded that the awareness of digital financial literacy would greatly help from debt traps by means of the loan application. Accordingly, Islamic studies became very relevant to the phenomenon in the Maqasid Sharia law, such as Hifdz al Maal, which also discussed economic security from an Islamic view. The correlation between the phenomenon would be best analyzed with both concepts to reduce harm to economic security, structurally and religiously. On the other hand, the lack of socialization in digital economy transactions threatens the security of people nowadays. The research used mix method approach with secondary and primary data. The primary data were obtained from the questionnaire from 61 samples from 17 years old Indonesian, then delivered in descriptive statistics to see the fact for real, while the secondary data was obtained from journals, books, and articles. The analysis determined the correlation between digital financial phenomena in the Maqosid Sharia Concept and human security.